Headache as the most prevalent post-vaccination adverse event after Covid-19 vaccination - Freitas, Francisco Ricardo Nascimento; Júnior, Edmar José Fortes; Freitas, Débora Joyce Nascimento; Caproni, Samara Menali Pereira; Barros, Daniela França de; Neto, Raimundo Pereira da Silva (Headache Medicine, 2024)
Context:  In 2020, the first vaccines were approved, according to the WHO. However, speculations have arisen regarding its efficacy and post-vaccination adverse events (AEFI). Objective: To evaluate the prevalence of headache as AEFI from the SARSCoV-2 vaccine in Piauí, Brazil.Methods: This is a quantitative, observational, cross-sectional and prevalence study. The data were provided by the Post-Vaccination Adverse Events Information System (SI-AEFV), of cases reported in the period from January to September 2021. The data were analyzed and the research was approved by the Research Ethics Committee of the UFPI. Results:  2,008 cases were analyzed. Headache was reported in 752 cases (27.99%) as AEFI after vaccination against SARS-CoV-2. In most cases, the patients were from Teresina (67.62%), of mixed race/ethnicity (52.67%), female (79.00%) and the majority were not healthcare professionals (54. 27%). The most common age of patients, with the original data, was 33 years old. After correcting the data, the most common age was 28 years old. The majority of these cases were not serious (96.44%) and the majority of cases were associated with the first dose of the Covid-19-Covishield-Oxford/AstraZeneca vaccine (43.18%). Conclusion: Thus, it is concluded from the partial analysis of the results that headache is the most common adverse event after vaccination against SARS-CoV-2. The profile of patients with the most notifications was mixed-race women aged between 30 and 40 years who received the first dose of the Covid-19-Covishield-Oxford/AstraZeneca vaccine. Regarding the severity of the events, the vast majority were considered non-serious and no deaths were mentioned, demonstrating the safety of immunobiologicals.